A Gran Amazonía no século 21: infraestruturas e desafios da integração em múltiplas escalas - Thais Virga; Wanderley Messias da Costa (Confins)
The issue of transport infrastructure in Gran Amazonía involves a complexity of actors and socio-spatial dimensions that give this immense region a prominent role in the face of multiple scales of actions and impacts that transform it in an unprecedented way in this century. The text examines the recent advance of foreign investments in large projects and undertakings linked to the transport sector, alongside the internal and local demands for circulation and accessibility, a framework that involves objectives that are not always convergent, deadlocks and conflicts that have not yet been analyzed on these scales. The approach adopted considers all scales at stake, but deliberately highlights the importance of the regional scale, since this is increasingly decisive in understanding the complexity inherent to the question of infrastructure in the Amazon. By highlighting the region's current position in international logistics and the role of circulation infrastructures in local development, it is considered that the regional scale is directly and indirectly associated with the others, illuminating realities of multiple spatial dimensions that make up the process of Amazonian physical integration and subcontinental. Thus, a more integrated and strategic vision of transport in Gran Amazonía is highlighted in the face of impasses that penetrate borders and development opportunities that could be better used in the region and in South America itself.